O ethos pós-moderno, pensamento fraco e a ética pós-metafísica na sociedade transparente de Gianni Vattimo - Silva, Adelino Pereira da (2022)
We propose a study about how the philosophical thought of Gianni Vattimo is inserted in the context of the contemporary philosophy, from his formulation of the pensiero debole (weak thought), as a contribution, in the last decades, to the critical-philosophical discussion in the world, endorsing this period as Post-Modern (or the, namely, Post-modernity). The objective is a discussion through which we understand the current society as marked by the “generalized communication”, i.e, through the intense experience of the mass media, in view of the debate in face of the idea of the post-modern, according to what is proposed by Gianni Vattimo. In this regard, we propose the hypothesis that there is a post-metaphysical ethics in the society of mass media, that are inserted in Vattimo’s reflection on the post-modern– and, consequently, in the debate about the crisis of reason and the abandonment of the, namely, ‘strong’ structures, from the work The Transparent Society, as well as the deliberation about a crisis of the Metaphysics, in addition to the crisis of the totalizing legitimacy of the meta-reports and the statement of the thesis of the ‘end’ of modernity. All this implies in a(n) (re)interpretation of some of the border problems that can be alleviated through the sense of a post-modern ethos. Wherefore, the topic, and the hypothesis, that guides this work are not limited to the acknowledgement of ethics as a current phase of thought, but, mainly, it defends the ethics as the fundamental motivation for the philosophical production of the Italian thinker, notedly as a post-metaphysical ethics in a transparent society. This post-metaphysical ethics, in the context of the media, encourages the critical-philosophical reflection on the new experiences given by the globalized communication and by the new worldviews and the cultures of dialects, as well as by the appearance of the cultures of the minorities, through the informational progress, helping us realize that the ethical motivation is rooted, mainly, in the distancing of the metaphysical “violence” in order to ideate a post-modern ethics, which abandons, for example, the universalist, absolute criteria of the metaphysics ethics – and this, outwardly, thanks to the opening that the mass media promote for the aforementioned post-modern ethics, emphasizing the culture of dialects and of differences as a new ethics field.